A DISCOURSE OF REPATRIATION OF INDONESIAN EX-ISIS CITIZENS “Law, Human Rights, and Socio-Politics Consideration” - Irwansyah,; Edy, Susilo; Hapsoro, Suryo; Sulaiman, Ahmad; Ridwan, M. Mujib (International Journal of Psychosocial Rehabilitation, 2020)
Pros and cons of the discourse of repatriation of Indonesian ex-ISIS citizens create a dilemma for the Indonesian government. The government has to determine the positive and negative impacts of the decisions to be taken. This research seeks to explore the discourse of repatriation of Indonesian ex-ISIS citizens from the perspective of law, human rights, and socio-political impacts and risks in Indonesia, as well as providing recommendations for policy considerations for the government. Using a case study method and secondary data, it was concluded that the Indonesian government has legal bases regarding the decision to be taken. From the perspective of human rights, the government also has reasons for taking all policies except neglecting children and families of ex-ISIS combatants. The policy recommendations are to repatriate children and families and provide a process of deradicalization and encourage international legal processes for ex-ISIS combatants involved.